FENOMENA PEMANFAATAN TIKTOK SHOP SEBAGAI MEDIA BELANJA ONLINE DI KALANGAN MASYARAKAT KECAMATAN BAROS KABUPATEN SERANG (STUDI KASUS DESA SUKA INDAH) - usy rahmawati (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study aims to understand the use of TikTok Shop as an online shopping platform among residents of Sukaindah Village, Baros District. This study applies a qualitative approach with descriptive methods. Data collection was conducted through observation, interviews, and document collection with informants selected using a purposive sampling technique. The research findings indicate that TikTok Shop facilitates access, offers quite affordable prices, and various attractive promotions such as discounts and free shipping, thus encouraging people to shop online. In addition, the live broadcast feature is a major attraction because it allows direct interaction between sellers and buyers. The use of TikTok Shop also influences changes in people’s consumption patterns, as seen from increased ease of shopping and product knowledge, as well as the emergence of consumptive behaviors such as unplanned purchases, wastefulness, and a tendency to follow trends. Therefore, TikTok Shop not only functions as a transaction facility, but also influences people’s mindsets and lifestyles in fulfilling their needs and desires.